2015
DOI: 10.3390/nu7125537
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Antiproliferative and Pro-Apoptotic Effects of 5-Hydroxyl-6,7,3′,4′,5′-Pentamethoxyflavone Isolated from Lantana ukambensis

Abstract: Lantana ukambensis (Vatke) Verdc. is an African food and medicinal plant. Its red fruits are eaten and highly appreciated by the rural population. This plant was extensively used in African folk medicinal traditions to treat chronic wounds but also as anti-leishmanial or cytotoxic remedies, especially in Burkina Faso, Tanzania, Kenya, or Ethiopia. This study investigates the in vitro bioactivity of polymethoxyflavones extracted from a L. ukambensis as anti-proliferative and pro-apoptotic agents. We isolated tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Indeed, this study concluded that Vitexdoniana fruit pulp could be promoted as: carbohydrate and lipid supplements for cereal-based diets inrural communities [39]. Sawadogo et al [3] have quantified some metal ions (Na + and K + ) and showed th.eir implication in the Na + -K + -pump action.…”
Section: Ions Quantificationmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, this study concluded that Vitexdoniana fruit pulp could be promoted as: carbohydrate and lipid supplements for cereal-based diets inrural communities [39]. Sawadogo et al [3] have quantified some metal ions (Na + and K + ) and showed th.eir implication in the Na + -K + -pump action.…”
Section: Ions Quantificationmentioning
confidence: 82%
“…Thus we couldn't find the derivative luteolin and rutin [1] in our extracts. Other researchers showed in the dichloromethane fractions of L. rhodesiensis, two flavonoids such as 5,6,7,3',4',5'hexamethoxyflavone and its analogue, 5-hydroxy-6,7,3',4',5'pentamethoxyflavone [3]. The most elucidated studies on L. chevalieri, L. rhodesiensis, V. diversifolia and V. donianaespecially related to their content of essential oils [1], [3], [5], [8].…”
Section: Hplc-dad Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Limited data are available on this flavone. The few studies report its isolation from Lantana ukambensis, Citrus reticulate and A. conyzoides, and its cytotoxicity against P-388 mouse lymphocytic leukemia and A549 lung carcinoma cells, and inhibition of histamine release in RBL-2HR cells (Adebayo et al, 2010;Sawadogo et al, 2015;Itoh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Roots are boiled in water and drunk for rheumatism and generalized body pains [4][5][6][7][8][9][10][11][12][13][14]. Especially in Burkina Faso, L. rhodesiensis is used in folk medicine to treat chronic wounds and skin diseases [15]. Accordint toTeketay et al [13], leaf ofL.…”
Section: Introductionmentioning
confidence: 99%